2022
DOI: 10.1016/j.metop.2021.100160
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric extract alleviates endocrine-metabolic disturbances in letrozole-induced PCOS by increasing adiponectin circulation: A comparison with Metformin

Abstract: One of the most common causes of female infertility is polycystic ovarian syndrome, which affects 6–21% of the population. Regrettably, the currently available treatments are mostly symptomatic and ineffective. As a result, safer options are needed now more than ever. In a letrozole PCOS albino mouse model, the current study compares the therapeutic advantages of Turmeric extract (Curcuma longa) to metformin. Adiponectin is a circulating protein generated by adipocytes that has been linked to metabolic disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…Serum androgen levels were elevated in PCOS-affected mice, which was the most consistent hormonal trait. Increased testosterone and LH and reduced estrogen, FSH, and progesterone have also been noted in PCOS-afflicted mice [ 39 , 40 ]. In this investigation, in contrast to levels in PCOS-afflicted mice, CGA decreased serum testosterone, LH, and LH/FSH concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Serum androgen levels were elevated in PCOS-affected mice, which was the most consistent hormonal trait. Increased testosterone and LH and reduced estrogen, FSH, and progesterone have also been noted in PCOS-afflicted mice [ 39 , 40 ]. In this investigation, in contrast to levels in PCOS-afflicted mice, CGA decreased serum testosterone, LH, and LH/FSH concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its multidimer forms, adiponectin plays a variety of roles [12] . Nevertheless, its diminished secretion and the accompanying low levels of circulating adiponectin have been linked to metabolic issues including PCOS [13] , [14] . Furthermore, it has been found that visceral adiposity and adipocyte mass, two significant risk factors for metabolic and related disorders, have inverse relationship with the circulating adiponectin [15] , [9] , suggesting increasing visceral adiposity decreases its concentration.…”
Section: Introductionmentioning
confidence: 99%
“…PCOS has been studied experimentally in rats using a variety of methods, including the injection of DHEA, excess prepubertal androgen, and estradiol valerate [13] . These models all produce PCOS, but none of them are completely convincing or precisely match the symptoms of real PCOS.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperandrogenism is characterized by a hormonal imbalance, chronic menstrual dysfunction (oligo- or anovulation), impaired fertility, hirsutism (excessive body hair growth), acne, obesity, diabetes mellitus, metabolic disturbances (dyslipidemia, hyperinsulinemia, insulin resistance, and type 2 diabetes), increased incidence of endometrial hyperplasia and cancer, and policy [ 3 ]. Polycystic ovary syndrome affects around 6–20% of women of reproductive age, and its incidence is on the rise and is the leading cause of female infertility [ 4 , 5 ]. Polycystic ovary syndrome can disrupt ovulation and can lead to infertility; as a result, it is not surprising that infertility affects 70–80% of women with PCOS [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone protects the uterus against estrogen-induced uterine development and proliferation [ 12 ]. The primary cause of glucose metabolic disease is insulin resistance (IR), which is also thought to be a key factor in the development of PCOS, which is strongly linked to concurrent metabolic difficulties [ 3 ].Low insulin sensitivity, often known as IR, is a syndrome that causes compensatory hyperinsulinemia and plays a significant role in the etiology of type 2 diabetes [ 4 ]. Increased levels of testosterone and luteinizing hormone are released as a result of hyperinsulinemia, which disrupts the uptake and utilization of glucose and results in prolonged anovulation [ 9 ].Allopathic medications such as clomiphene citrate, metformin, letrozole, tamoxifen, and troglitazone are now the most well-known treatments for PCOS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%